2021
DOI: 10.1371/journal.pone.0253567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taping techniques on arch deformation in adults with pes planus: A meta-analysis

Abstract: Objective To investigate effects of taping techniques on arch deformation in adults with pes planus. Methods The following databases were searched up to March 2020, including Web of Science, Pubmed, EBSCO, CNKI and Cochrane Library. Heterogeneity and publication bias were assessed by I2 index and funnel plots, respectively. In addition, Cochrane scale was used to evaluate the quality of research. Results Navicular height for three antipronation taping techniques significantly increased immediately post tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…These data are in line with the study carried out by Cornwall, Mark W. and McPoil, Thomas G. on the relationship between static foot posture and foot mobility, which found that individuals with higher FPI values demonstrated greater mobility than those with lower FPI values [29]. In the 2021 meta-analysis performed by Meihua Tang and Lin Wang et al [30], all types of tape were found to significantly increase the height of the navicular immediately after taping compared to the baseline (p < 0.001); in the review by Melinda Franettovich et al [10], an 8 to 16% increase in navicular height was found. In our study, we found that there was an increase in the arch height with tape, compared to the reference values on neutral feet of 5.5% (p < 0.05); pronated, 7.9% (p < 0.001); and supinated, 7.7% (p < 0.05).…”
Section: Arch Heightsupporting
confidence: 89%
See 1 more Smart Citation
“…These data are in line with the study carried out by Cornwall, Mark W. and McPoil, Thomas G. on the relationship between static foot posture and foot mobility, which found that individuals with higher FPI values demonstrated greater mobility than those with lower FPI values [29]. In the 2021 meta-analysis performed by Meihua Tang and Lin Wang et al [30], all types of tape were found to significantly increase the height of the navicular immediately after taping compared to the baseline (p < 0.001); in the review by Melinda Franettovich et al [10], an 8 to 16% increase in navicular height was found. In our study, we found that there was an increase in the arch height with tape, compared to the reference values on neutral feet of 5.5% (p < 0.05); pronated, 7.9% (p < 0.001); and supinated, 7.7% (p < 0.05).…”
Section: Arch Heightsupporting
confidence: 89%
“…In the 2021 meta-analysis performed by Meihua Tang and Lin Wang et al [30], all types of tape were found to significantly increase the height of the navicular immediately after taping compared to the baseline (p < 0.001); in the review by Melinda Franettovich et al [10], an 8 to 16% increase in navicular height was found. In our study, we found that there was an increase in the arch height with tape, compared to the reference values on neutral feet of 5.5% (p < 0.05); pronated, 7.9% (p < 0.001); and supinated, 7.7% (p < 0.05).…”
Section: Arch Heightmentioning
confidence: 99%
“…Sung low dye (MLD). MLD was found better than ALD in maintaining the navicular height immediately when subjects walks for 10 minutes [12].…”
Section: Jinteakmentioning
confidence: 73%
“…There are numerous studies aimed at re-raising low MLA [14,25]. Ankle and foot taping is a common clinical intervention used to treat and prevent foot arch disorders [23]. Many different taping techniques have been introduced in the literature to limit excessive foot pronation.…”
Section: Discussionmentioning
confidence: 99%